PENGARUH DANA PIHAK KETIGA (DPK), BI RATE, DAN TINGKAT INFLASI TERHADAP PENYALURAN KREDIT BANK UMUM YANG TERDAFTAR DI BEI PERIODE 2021-2022 : (Studi pada Mahasiswa Institut Teknologi dan Bisnis Semarang Kampus I) - Krisnawati, Hani; Diva Prasiwi , Evina (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The aim of this research is to determine the influence of DPK, inflation and BIrate on credit distribution issued by commercial banks registered in Indonesian Stock Exchange 2021-2022. The population in this research is all banking company data which are listed on the Indonesia Stock Exchange (BEI) from 2021 to 2022,as many as 47 companies (94 data). The research was carried out by sampling, using purposive sampling technique, a sample of 40 data was obtained. Method used is multiple linear analysis. The results of this research show that: 1) Third Party Funds (DPK) significant positive effect on credit distribution, 2) BI rate does not have influence on credit distribution, 3) Inflation has no influence on credit distribution..